2013
DOI: 10.1097/prs.0b013e3182789c02
|View full text |Cite
|
Sign up to set email alerts
|

Repair of Facial Scars by the Free Expanded Deltopectoral Flap

Abstract: Therapeutic, V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…One of the most commonly used flaps around the anterior chest region has been historically represented by the deltopectoral flap, and extensive pioneering works have documented its use in the treatment of cervicofacial defects . However, some disadvantages have limited this flap versatility over practice and have concurred to make this flap being considered almost outdated and progressively less used for oral cavity reconstruction according to modern reconstructive principles: short vascular pedicle with limited arch of rotation; long distance from the pivot point to the receiving site; time necessary (usually 3 weeks) to vascular delay; two‐step reconstruction required for challenging reconstructions; mandatory position of patients; sporadic need of a skin graft to cover the donor site, especially if the flap is harvested out of its angiosome .…”
Section: Discussionmentioning
confidence: 99%
“…One of the most commonly used flaps around the anterior chest region has been historically represented by the deltopectoral flap, and extensive pioneering works have documented its use in the treatment of cervicofacial defects . However, some disadvantages have limited this flap versatility over practice and have concurred to make this flap being considered almost outdated and progressively less used for oral cavity reconstruction according to modern reconstructive principles: short vascular pedicle with limited arch of rotation; long distance from the pivot point to the receiving site; time necessary (usually 3 weeks) to vascular delay; two‐step reconstruction required for challenging reconstructions; mandatory position of patients; sporadic need of a skin graft to cover the donor site, especially if the flap is harvested out of its angiosome .…”
Section: Discussionmentioning
confidence: 99%
“…Since the DP flap was first introduced by Bakamjian 1 in 1965, many authors have reported various reconstructions using the flap, 1 5 of which the donor site was mostly reconstructed using skin grafting. 1 , 2 We have also performed anterior neck region reconstruction using the DP flap.…”
Section: Discussionmentioning
confidence: 99%
“…Because of a good colour and texture match, pre-expanded local skin flaps would be advantageous especially in head and neck reconstruction 11,12 . Pre-expanded deltopectoral flap, subclavicular and supraclavicular flaps are able to obtain contour and colour match to the neck [13][14][15] . Major disadvantage of these flaps is the morbidity of the donor site that always leads to a hypertrophic scar.…”
Section: Discussionmentioning
confidence: 99%